Extreme Productivity : Boost Your Results, Reduce Your Hours
A road-tested formula for improving your performance, from one of the business world\\\'s most successfulâ€"and productiveâ€"executives.Robert C. Pozen taught a full course load at Harvard Business School while serving as the full-time chairman of a global financial-services firm. He\\\'s written six books and hundreds of articles, raised a family with his wife of more than four decades, and served on many boards of local charities and public companies. Pozen is a prince of productivity, a man who has worked smarter and faster than almost everyone around him for more than forty years.In Extreme Productivity, Pozen reveals the secrets to workplace productivity and high performance. His book is for anyone feeling overwhelmed by an existing workloadâ€"facing myriad competing demands and multiple time-sensitive projects. Offering antidotes to a calendar full of boring meetings and a backlog of e-mails, Extreme Productivity explains how to determine your highest priorities and match them with how you actually spend your time.Pozen shows that in order to be truly productive, professionals must make a critical shift in their mind-set: from hours worked to results produced. He helps people at all stages of their careers read, write, and make presentations quicker and more effectively. He provides professionals with practical tips on how to efficiently use their time in the officeâ€"while leading full and productive personal lives as well.